The HTN3-MSANTD3 Fusion Gene Defines a Subset of Acinic Cell Carcinoma of the Salivary Gland. (April 2019) - Andreasen, Simon; Varma, Sushama; Barasch, Nicholas; Thompson, Lester D.R.; Miettinen, Markku; Rooper, Lisa; Stelow, Edward B.; Agander, Tina K.; Seethala, Raja R.; Chiosea, Simion I.; Homøe, Preben; Wessel, Irene; et al.
Abstract : The spectrum of tumors arising in the salivary glands is wide and has recently been shown to harbor a network of tumor-specific fusion genes. Acinic cell carcinoma (AciCC) is one of the more frequently encountered types of salivary gland carcinoma, but it has remained a genetic orphan until recently when a fusion between the HTN3 and MSANTD3 genes was described in one case. Neither of these 2 genes is known to be implicated in any other malignancy. This study was undertaken to investigate whether the HTN3 - MSANTD3 fusion is a recurrent genetic event in AciCC and whether it is a characteristic of one of its histological variants. Of the 273 AciCCs screened, 9 cases showed rearrangement of MSANTD3 by break-apart fluorescence in situ hybridization, 2 had 1 to 2 extra signals, and 1 had gain, giving a total of 4.4% with MSANTD3 aberrations. In 6 of 7 available cases with MSANTD3 rearrangement, the HTN3 - MSANTD3 fusion transcript was demonstrated with real-time polymerase chain reaction. Histologically, all fusion-positive cases were predominantly composed of serous tumor cells growing in solid sheets, with serous tumor cells expressing DOG-1 and the intercalated duct-like cell component being CK7 positive and S-100 positive in 6/9 cases. All but one case arose in the parotid gland, and none of the patients experienced a recurrence during follow-up. In contrast, the case with MSANTD3 gain metastasized to the cervical lymph nodes and lungs. In conclusion, we find the HTN3 - MSANTD3 gene fusion to be a recurrent event in AciCC with prominent serous differentiation and an indolent clinical course.